A network meta‐analysis of the effects of psychotherapies, pharmacotherapies and their combination in the treatment of adult depression. Issue 1 (10th January 2020) - Cuijpers, Pim; Noma, Hisashi; Karyotaki, Eirini; Vinkers, Christiaan H.; Cipriani, Andrea; Furukawa, Toshi A.
Abstract : No network meta‐analysis has examined the relative effects of psychotherapies, pharmacotherapies and their combination in the treatment of adult depression, while this is a very important clinical issue. We conducted systematic searches in bibliographical databases to identify randomized trials in which a psychotherapy and a pharmacotherapy for the acute or long‐term treatment of depression were compared with each other, or in which the combination of a psychotherapy and a pharmacotherapy was compared with either one alone. The main outcome was treatment response (50% improvement between baseline and endpoint). Remission and acceptability (defined as study drop‐out for any reason) were also examined. Possible moderators that were assessed included chronic and treatment‐resistant depression and baseline severity of depression. Data were pooled as relative risk (RR) using a random‐effects model. A total of 101 studies with 11, 910 patients were included. Depression in most studies was moderate to severe. In the network meta‐analysis, combined treatment was more effective than psychotherapy alone (RR=1.27; 95% CI: 1.14‐1.39) and pharmacotherapy alone (RR=1.25; 95% CI: 1.14‐1.37) in achieving response at the end of treatment. No significant difference was found between psychotherapy alone and pharmacotherapy alone (RR=0.99; 95% CI: 0.92‐1.08). Similar results were found for remission. Combined treatment (RR=1.23; 95% CI: 1.05‐1.45) and psychotherapy alone (RR=1.17; 95% CI: 1.02‐1.32) were more acceptable than pharmacotherapy. Results were similar for chronic and treatment‐resistant depression. The combination of psychotherapy and pharmacotherapy seems to be the best choice for patients with moderate depression. More research is needed on long‐term effects of treatments (including cost‐effectiveness), on the impact of specific pharmacological and non‐pharmacological approaches, and on the effects in specific populations of patients.